Effects of child characteristics on the Autism Diagnostic Interview-Revised: Implications for use of scores as a measure of ASD severity - Hus, Vanessa (2013)
The Autism Diagnostic Interview-Revised (ADI-R) is commonly used to inform diagnoses of autism spectrum disorders (ASD). Considering the time dedicated to using the ADI-R, it is of interest to expand the ways in which information obtained from this interview is used. The current study examines how algorithm totals reflecting past (ADI-Diagnostic) and current (ADI-Current) behaviors are influenced by child characteristics, such as demographics, behavioral problems and developmental level. Children with less language at the time of the interview had higher ADI-Diagnostic and ADI-Current. ADI-Diagnostic totals were also associated with age; parents of older children reported more severe past behaviors. Recommendations are provided regarding the use of the ADI-R as a measure of ASD severity, taking language and age into account.